Process Approach Used by Students in Essay Writing at English Departmant - Indah Rahmalia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to find out the process approach used by students in essay writing at STKIP AbdiPendidikanPayakumbuh. This study was carried out of descriptive research by employing questionnaire consist of 24 questions to 13 students in the secondacademic yearselected by using purposive sampling technique. The results of this study indicate that students have used all the process approach in essay writing. The most dominant process used by students is brainstorming with scores (111) and the least used by students is feedback with scores (84). From the result, It can be concluded that all students used the process approach in essay writing. Keywords: process approach, writing, essay writing